2011
DOI: 10.1002/eji.201141597
|View full text |Cite
|
Sign up to set email alerts
|

1,25‐Dihydroxyvitamin D3 enhances NK susceptibility of human melanoma cells via Hsp60‐mediated FAS expression

Abstract: The active metabolite of vitamin D 3 , 1a,25(OH) 2 D 3 , displays anticancer effects by regulating cell cycle and apoptosis in many cancer cells. However, it has not been determined whether 1a,25(OH) 2 D 3 increases the susceptibility of cancer cells to NK cells. Here, we investigated the anticancer effect of 1a,25(OH) 2 D 3 in human melanoma cell lines by investigating enhancement of NK susceptibility and elucidating the mediator of NK cytotoxicity. 1a,25(OH) 2 D 3 -resistant melanoma cells (G-361 and SK-MEL-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 59 publications
1
15
0
Order By: Relevance
“…Lee et al . showed that vitamin D 3 activates NK cells to kill melanoma cells, an activity related to FAS up-regulation and induction of apoptosis [36]. In another study it was shown that NK cells by releasing IL-8 recruit eosinophils in allergic rhinitis, an effect that is inhibited by vitamin D 3 , indicating that this vitamin may play an important role as an anti-inflammatory molecule [37].…”
Section: Discussionmentioning
confidence: 99%
“…Lee et al . showed that vitamin D 3 activates NK cells to kill melanoma cells, an activity related to FAS up-regulation and induction of apoptosis [36]. In another study it was shown that NK cells by releasing IL-8 recruit eosinophils in allergic rhinitis, an effect that is inhibited by vitamin D 3 , indicating that this vitamin may play an important role as an anti-inflammatory molecule [37].…”
Section: Discussionmentioning
confidence: 99%
“…Studies in VDR knockout mice have shown that expression of VDR is necessary for NK cell development and function [114]. 1a,25(OH) 2 D enhances NK cell cytotoxicity [115] and suppresses DC maturation, inducing a more tolerant DC phenotype which, at the interface of the innate and adaptive immune systems, promotes T regulatory (Treg, CD4+CD25+) cell activity [116].…”
Section: Innate Immunitymentioning
confidence: 98%
“…Recent investigations show that 1,25(OH)2D3 reduces the number of CPDs in human keratinocytes after UV-B radiation (Lee and Youn, 1998; De Haes et al, 2004; Trémezaygues et al, 2006). Interestingly Lee et al (2011) demonstrated that calcitriol exert anticancer effects enhancing natural killer (NK) cells susceptibility of human melanoma cells lines: 1,25(OH)2D-resistant melanoma cells treated with 1,25(OH)2D showed higher susceptibility to NK cells via heat shock protein 60 (Hsp60)-mediated up-regulation of FAS expression. Melanoma cells, in addition to expressing the VDR, are able to synthesize 1,25(OH)2D from 25(OH)D and proliferate much more slowly in the presence of calcitriol.…”
Section: Vitamin D and Melanomamentioning
confidence: 99%